Asset divestiture following horizontal acquisitions: a dynamic view - Capron, Laurence; Mitchell, Will; Swaminathan, Anand (Strategic Management Journal, 2001)
Abstract Business acquisition, resource redeployment, and asset divestiture are elements of a dynamic process in which firms change their businesses by recombining internal and external resources. Analyzing 253 horizontal acquisitions, we show that post‐acquisition resource redeployment leads to asset divestiture from the business that receives the redeployed resources, but not from the business that contributes the new resources. Consistent with scale economies rationales, we find that strategic similarity also leads to greater asset divestiture from the target firms. Many theoretical perspectives are skeptical about the positive rationale for acquisitions and many of these believe that asset divestiture is evidence of acquisition failure. Our arguments and analysis help refine the accepted wisdom. In particular, the pattern of resource redeployment and asset divestiture in our analysis suggests that acquisitions provide a means of reconfiguring the structure of resources within firms and that asset divestiture is a logical consequence of this reconfiguration process. Copyright © 2001 John Wiley & Sons, Ltd.